Factors Associated with Health Supplement Consumption Behavior of People Surveyed in Phung Thuong Commune, Phuc Tho District, Hanoi City, in 2022 - Xuan Bach, Nguyen; Thi Thu Thuy, Can; Thi Huong Thao, Nguyen; Dang Tuan, Mac; Ngoc Ha, Vu (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 4, 2025)
Abstract: Objective: To analyze some factors related to the consumption behavior of health supplements among people in Phung Thuong commune, Phuc Tho district, Hanoi city. Research subjects: People in Phung Thuong commune who met the selection criteria (had registered residence in the commune for 1 year or more, lived and worked in the commune, could answer interviews or fill out survey forms, and voluntarily participated in the study). Research method: A cross-sectional study was conducted on 197 people in Phung Thuong commune, selected by convenience method, and surveyed by a self-completed questionnaire via Google Form. Results: Factors related to consumption behavior included marital status, interest in health, and the absence of subjects needing special care in the family. Conclusion: The study discovered some factors related to the consumption behavior of the research subjects. From there, it is possible to suggest measures to adjust people's behavior, focusing on groups with related factors. Keywords: Behavior, health supplement, Phung Thuong commune.